2022
DOI: 10.1002/1878-0261.13166
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIIa receptor interacts with androgen receptor and PIP5K1α to promote growth and metastasis of prostate cancer

Abstract: Low-affinity immunoglobulin gamma Fc region receptor III-A (FccRIIIa) is a cell surface protein that belongs to a family of Fc receptors that facilitate the protective function of the immune system against pathogens. However, the role of FccRIIIa in prostate cancer (PCa) progression remained unknown. In this study, we found that FccRIIIa expression was present in PCa cells and its level was significantly higher in metastatic lesions than in primary tumors from the PCa cohort (P = 0.006). PCa patients with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For example, USP16, KDM4B, and RNF8 could regulate AR signaling by mediating the expression of c-myc (6)(7)(8). Interestingly, Larsson et al found that FcgRIIIa receptors could interact with AR receptors and affect the progression of CRPC in xenograft mouse models (9). COP1 promoted GATA2 degradation to inhibit AR expression and activation (10), however, Shen et al found that MAPK4 activated GATA2 to regulate AR transcription in mice (11).…”
Section: Crpc Carcinogenesis and Clinical Intervention Strategies Ar-...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, USP16, KDM4B, and RNF8 could regulate AR signaling by mediating the expression of c-myc (6)(7)(8). Interestingly, Larsson et al found that FcgRIIIa receptors could interact with AR receptors and affect the progression of CRPC in xenograft mouse models (9). COP1 promoted GATA2 degradation to inhibit AR expression and activation (10), however, Shen et al found that MAPK4 activated GATA2 to regulate AR transcription in mice (11).…”
Section: Crpc Carcinogenesis and Clinical Intervention Strategies Ar-...mentioning
confidence: 99%
“…Interestingly, Larsson et al. found that FcγRIIIa receptors could interact with AR receptors and affect the progression of CRPC in xenograft mouse models ( 9 ). COP1 promoted GATA2 degradation to inhibit AR expression and activation ( 10 ), however, Shen et al.…”
Section: Crpc Carcinogenesis and Clinical Intervention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation